STRATEGI PELAYANAN PUBLIK DI KANTOR KECAMATAN KANDANGAN KABUPATEN KEDIRI - Fachruddin, Imam (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
This study aims to determine the performance of the apparatus, the strategy of improving public services in Kandangan Subdistrict, Kediri Regency, as well as obstacles faced to strengthen public service capacity in the Kandangan District Office, Kediri Regency. This research is a descriptive study using a qualitative approach. Data collection techniques are carried out with observation, interview, and documentation techniques. Data analysis techniques used are interactive models. The validity of the data is done by triangulating the source and method. Utilizing the information from the informants, this study produced findings: 1). The public service strategy in the Kandangan District Office is seen from various indicators, namely the provision of physical facilities and equipment, reliability, simplification of processes, pure responsiveness of the apparatus, providing waiting rooms and places. Secure parking/assurance (Assurance), and empathy (empathy) apparatus in Kandangan Subdistrict, the average community considers it to be relatively good. 2). Sensitivity to the community, enhancing the professionalism of apartments and supplementing infrastructure - the strategy of the government of Kediri Regency in Improving the Quality of the Implementation of Public Services in Kandangan sub-district.